A Case of Surgically Intervened Chronic Tophaceous Gout and Review of Literature - Sinha, Siddhartha (J Orthop Case Rep, 2020)
BACKGROUND: Gout is a disease of deposition of monosodium urate crystal in the body which commonly presents as an acute arthritis of the peripheral joints but can have varied presentation. It is mostly managed by dietary modifications and drugs, but surgery is rarely required for the management of urate crystals. CASE REPORT: We present a case of a 66-year-old male who intermittently presented to the outpatient with multiple tophi which was managed with lifestyle changes and medically; initially, the patient eventually required surgical excision for tophi in fingers and heel which improved the pain and morbidity of the patient. CONCLUSION: Gout can be managed by lifestyle changes, medically by drugs, and in extreme cases surgically and requires the utmost compliance by the patient. Such surgical intervention is rare with the advent of uricosuric medication now.